An empirical study for blockchain-based information sharing systems in electronic health records: A mediation perspective. (January 2023) - Hajian, Ava; Prybutok, Victor R.; Chang, Hsia-Ching
Abstract: Electronic health record (EHR) systems have a considerable impact on reducing healthcare costs by offering better disease management and fewer medical errors, while current systems fail to encourage the majority of patients to share their health records. Blockchain is a reliable alternative among the options to improve current systems. Little is known about whether blockchain-based health information systems contribute to healthcare networks regarding patients' intention to share their health records. In particular, there is no empirical research documenting patients' behavior in blockchain-based EHR systems. This study involved an experimental designed to contribute to prior research by examining how blockchain can be related to patients' behavior with EHR systems. Confirmatory factor analysis is used for the validity and reliability tests of the model. Moreover, this research addressed the endogeneity problems using two-stage least squares regression analysis. Results were based on regression analysis and structural equation modeling. The results show that blockchain-based information systems can empower patients by providing the perception of control over their health records. The usage of blockchain technology motivates patients to share information with healthcare provider systems and has the advantage of reducing healthcare costs and improving diagnosis management. Highlights: Electronic health record (EHR) systems reduce healthcare costs. Blockchain is a reliable alternative among the options to improve EHR systems. Blockchain-based health information systems contribute to healthcare networks. Empowering patients, blockchain increases their intention to share their records. Blockchain-based information systems can empower patients.